Biliary atresia recent insight - Ramy Mohamed Ghazy; Nermin M. Adawy; Mohamed Ahmed Khedr; Mohamed Mostafa Tahoun (SpringerOpen, 2018)
Biliary atresia (BA) is a rare disease characterized by ascending obstruction of bile ducts that exclusively affects newborn infants. The etiology of the disease is not known. BA is considered to be a phenotype resulting from several pathogenic processes leading to obstruction of the biliary tree. It usually presents shortly after birth, characterized by persistent jaundice, hepatosplenomegaly, clay-colored stool, and dark urine. It affects both the extra-hepatic biliary ducts (EHBDs) and the intra-hepatic biliary system (IHBDs), but the former is more severely affected. Diagnosis of BA is a great challenge and must be achieved as early as possible to delay progression to cirrhosis. Laboratory tests reveal direct hyperbilirubinemia and, variable levels of transaminases, gamma-glutamyl transpeptidase (GGT), and alkaline phosphatase (ALP), which overlap significantly with other causes of neonatal cholestasis. The intraoperative cholangiogram is considered the gold standard for the diagnosis of BA and is performed routinely in many institutions. BA can be divided into correctable and non-correctable types; the former accounts for (10-15%) of cases, in which the proximal common hepatic duct is patent, allowing primary anastomosis of the EHBDs to the bowel. All patients are subjected to identical surgical and medical treatments; consisting of Kasai portoenterostomy (KPE), which entails removal of the atretic extra-hepatic tissue and a Roux-en-Y jejunal loop anastomosed to the hepatic hilum. Kasai portoenterstomy is considered a transition to liver transplantation, as the pathology may be still ongoing. BA is the most frequent indication for liver transplantation in infants, which is the only treatment that can definitively arrest the natural disease course. In conclusion: BA is a serious liver disease that needs to be further studied, and awareness of BA should be increased among the public and health care workers to prevent the complications of this disease.